Soluble HLA-G is related to malignant melanocytic lesions and previous oncological disease may increase circulating HLA-G bearing large extracellular vesicles - Silva-Krebs, Kianny Kimberly; de Oliveira, Evelyn Maciel; Athayde, Carlos Arthur; da Fonseca, Pedro Barbosa; De Felice, Fernanda G.; Carvalho, Fabiana Rabe; Sá Araújo, Marcelo; Luz, Flávio Barbosa; Silva, Andrea Alice; Pantaleão, Luciana; Medeiros, Thalia; Dayse-Silva, Istéfani Luciene (Frontiers in Immunology, 2025)
IntroductionHuman leukocyte antigen G (HLA-G) can induce tumor immune escape, facilitating tumor progression. Extracellular vesicles (EVs) are also involved in tumor progression, due to its activity on metastatic niche preparation and immune system modulation. However, the role of EVs bearing HLA-G, on its surface or cargo, is still few explored.MethodsIn this cross-sectional study, participants with benign (nevi) and malignant melanocytic lesions were recruited. Plasma large EVs (LEVs, 100-900nm) were isolated by differential centrifugation and analyzed by nanoscale flow cytometry, nanoparticle tracking analysis (NTA) and transmission electron microscopy (TEM). Plasma soluble HLA-G (sHLA-G) and intravesicular HLA-G (int-HLA-G) were measured by ELISA.ResultsWe included 68 patients (37 melanoma and 31 nevi), presenting a mean age of 57.9 ± 15.7 years-old and 67.6% were female. No differences were seen for particle count and size by NTA (p>0.05), or for total LEVs between benign and malignant lesions (p=0.8); however, sHLA-G levels were significantly higher in melanoma (p=0.02). Among patients with benign lesions, previous neoplasm was related to higher LEVs-HLA-G+ count (p=0.001) and int-HLA-G levels (p=0.03). Nevertheless, LEVs-HLA-G+ seems to be related to melanoma subtypes, especially with acral lentiginous melanoma. Moreover, sHLA-G was elevated in melanoma with head and neck localization (p=0.001). A preliminary in vitro assay showed that HLA-G may increase IL-6 secretion by leukocytes in the same way that plasma-derived LEVs from melanoma patients.DiscussionThese results may suggest that sHLA-G may be a promising biomarker to predict malignant melanocytic lesions; however, it is important to consider previous neoplasms. Also, its application may be relevant for specific histological subtypes and lesion sites.